2015
DOI: 10.2105/ajph.2015.302819
|View full text |Cite
|
Sign up to set email alerts
|

“We’re Part of the Solution”: Evolution of the Food and Beverage Industry’s Framing of Obesity Concerns Between 2000 and 2012

Abstract: We investigated how industry claim-makers countered concerns about obesity and other nutrition-related diseases in newspaper coverage from 2000, the year before the US Surgeon General's Call to Action on obesity, through 2012. We found that the food and beverage industry evolved in its response. The defense arguments were made by trade associations, industry-funded nonprofit groups, and individual companies representing the packaged food industry, restaurants, and the nonalcoholic beverage industry. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 46 publications
4
68
0
Order By: Relevance
“…However, given the emphasis the industry places on the difficulties and length of time needed to undertake reformulation -in this analysis and others (Webster et al 2011; National Heart Foundation of Australia 2012) -it is unlikely that they would have taken such voluntary reformulation actions if the threat of policy change were not already present in the early 2000s. Furthermore, these findings align with previous research showing that the food and beverage industry has shifted their framing of obesity overtime to encompass being 'part of the solution' (Nixon et al 2015). Moreover, although we recognize it is not possible to directly compare the tobacco and food industries, previous research on the tobacco industry mirrors and supports the results of this analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, given the emphasis the industry places on the difficulties and length of time needed to undertake reformulation -in this analysis and others (Webster et al 2011; National Heart Foundation of Australia 2012) -it is unlikely that they would have taken such voluntary reformulation actions if the threat of policy change were not already present in the early 2000s. Furthermore, these findings align with previous research showing that the food and beverage industry has shifted their framing of obesity overtime to encompass being 'part of the solution' (Nixon et al 2015). Moreover, although we recognize it is not possible to directly compare the tobacco and food industries, previous research on the tobacco industry mirrors and supports the results of this analysis.…”
Section: Discussionsupporting
confidence: 88%
“…From this smaller sample of articles (n=292), 15 were randomly selected to be read in-depth and qualitatively analyzed (open coding) by one researcher (CS) to develop the initial coding framework specific to this study. This initial coding frame was also informed by previous studies assessing food and beverage policy framing, which have found that the industry positions themselves as "part of the solution" to obesity and NCDs, and that nutrition is frequently framed as a matter of individual responsibility (Nixon et al 2015;Kersh 2009;Ken 2014;Jou et al 2014). A second researcher (LN) tested the validity of this initial coding framework by applying it to a further 8 randomly selected articles, and the framework was refined accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Most private sector interests focused on communicating values and consistently depicted themselves as a ‘vulnerable’ collection of small, family-run businesses that supported healthy and informed consumers. Consistent with prior content analyses ( 12 , 36 ) , many private sector restaurants congratulated themselves on advancing public health through current policies and many advocated for voluntary self-regulation related to menu labelling. This is consistent with a recent content analysis of the food and beverage industry’s framing of obesity in the news, which identified a shift in recent years away from framing obesity as an issue of personal responsibility and towards the message that the food and beverage industry wants to be ‘part of the solution’ ( 12 ) .…”
Section: Discussionmentioning
confidence: 72%
“…Consistent with prior content analyses ( 12 , 36 ) , many private sector restaurants congratulated themselves on advancing public health through current policies and many advocated for voluntary self-regulation related to menu labelling. This is consistent with a recent content analysis of the food and beverage industry’s framing of obesity in the news, which identified a shift in recent years away from framing obesity as an issue of personal responsibility and towards the message that the food and beverage industry wants to be ‘part of the solution’ ( 12 ) . Public health should be wary of industry claims of self-regulation, as research suggests that these self-regulatory programmes have not been very impactful ( 38 , 39 ) .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation